Health-Related Quality of Life in Rugby Athletes: The Role of Dietary Supplements and Their Consumption - Walter Sapuppo; Antonietta Monda; Davide Giacconi; Regina Gregori Grgič; Daniele Saccenti; Claudia Maria Mineo; Vincenzo Monda; Salvatore Allocca; Maria Casillo; Marcellino Monda; Girolamo Di Maio; Marco La Marra (MDPI AG, 2024)
This study investigates dietary supplement use among rugby players and their general health, focusing on prevalence and underlying motivations. Involving 92 athletes, it examines the relationship between supplement usage, motivations, and health outcomes using the 36-item Short Form Health Survey and a 24-item ad hoc questionnaire. Findings reveal a high frequency of supplement usage, motivated by desires to enhance performance, appearance, and mood. Significant differences in health-related quality of life are found between users and non-users, particularly in mental health, social functioning, and emotional stability. Motivations like performance enhancement and body shape manipulation were linked to altered health perceptions, indicating the psychosocial impacts of supplementation. This study emphasizes the need to consider the holistic effects of supplements on athlete well-being, advocating for a balanced approach prioritizing both physical and mental health. It calls for increased awareness among athletes, coaches, and sports professionals about the potential risks and benefits of supplement use and the importance of informed decision-making. Additionally, it highlights the need for further research to understand the mechanisms of supplement use and its impact on athlete health, aiming to enhance sports science and promote overall athlete well-being in competitive environments.